2017
DOI: 10.1016/j.triboint.2017.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of plasticity-based wear damage in gross sliding fretting of a Ti-6Al-4V non-conforming contact

Abstract: This paper examines the evidence for a plasticity based wear mechanism in the fretting wear of Ti-6Al-4V. Driven by near-surface plastic strain accumulation, the generation of wear debris evolves from coarse metallic debris towards loose fine oxide debris generating W-shape wear scar. The overall wear effect however, is less pronounced at the later stages of wear due to a reduced propensity for plastic deformation in the contact associated with wear induced contact pressure reduction. The evidence suggests tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…This sticking clearly shows that the accumulation of plasticity has not yet formed the wear debris so the wear width, wear area and the hardness are still low as compared to high frequency 2.5 Hz. At high frequency, the plasticity accumulation completely turns into wear debris therefore less sticking formed especially at the end left and right of the wear track [3].…”
Section: Vicker's Micro Hardnessmentioning
confidence: 99%
See 1 more Smart Citation
“…This sticking clearly shows that the accumulation of plasticity has not yet formed the wear debris so the wear width, wear area and the hardness are still low as compared to high frequency 2.5 Hz. At high frequency, the plasticity accumulation completely turns into wear debris therefore less sticking formed especially at the end left and right of the wear track [3].…”
Section: Vicker's Micro Hardnessmentioning
confidence: 99%
“…High performance of aero engine components experienced material wear losses resulting not only reduction to its performance but in some cases a complete failure of the components. Currently there is a limitation on life prediction of aero engine components due to inability to accurately predict the wear behavior for the components due to plasticity type deformation occurring on the contact pair [3].…”
Section: Introductionmentioning
confidence: 99%
“…The friction coefficient is depicted as a function of the number of cycles with logarithmic coordinates as shown in Figure 8, calculated by using the average amplitude Ti of a T-θ curve of each fretting cycle [42,43]. Generally, there are three typical stages that occur in the fretting running progress [44][45][46]. In the initial stage (stage I), the friction coefficients are relatively small, which could be due to two reasons: first, because of the protection and lubrication of fresh films on contacting surfaces; and second, because of the relative high roughness at very beginning of contact that causes a higher contact pressure, resulting in low friction [47,48].…”
Section: Friction Kinetics Behaviormentioning
confidence: 99%
“…Tobi et al. 15 studied the effect of plastic deformation on the fretting wear of Ti-6Al-4V alloy in the gross slip regime at the frequency of 20 Hz. It was found that under high load conditions, more plastic deformation occurred in the early fretting cycles, resulting in high wear rate.…”
Section: Introductionmentioning
confidence: 99%